THE THE TYPES OF CODE SWITCHING IN NESSIE JUDGE YOUTUBE CHANNEL - Ni Wayan, Anik Safitri (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
Abstract— This research is focused on the types of Code-Switching that found on Nessie Judge YouTube Channel. This study has specific aim which is to analyse the types of Code-Switching that used on Nessie Judge YouTube video. The data was collected from Nessie Judge YouTube videos on Nerror edition. Nessie Judge is one of Indonesian Youtuber which famous because of her consistency on her content and since 2012. The method that applied to in order to make sure the data analysis is clear is a theory from Appel and Musyeken (1987). The theory divided the types of Code-Switching into Tag Switching, Inter-Sentential Code-Switching, and Intra-Sentential Code-Switching. There are 60 data with 100% percentage found in Nessie Judge YouTube video and all of the types of code-switching have been found. The result of the analysis found there are 13 data (21.66%) using tag switching, 18 (30.00%) data found using inter-sentential code-switching, and 29 (48,33%) data found using intra-sentential switching. Keywords— Code-Switching, YouTube Channel, YouTube Videos.